Bolivia : Public Expenditure Management for Fiscal Sustainability and Equitable and Efficient Public Serivces - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER) - an update of the 1999 PER - is intended to provide recommendations that will allow Bolivia to regain control of its public finances, and further improve the equity, and efficiency of public services. The first part of the report looks at the macroeconomic setting and fiscal balance, significantly deteriorated in recent years, with an annual GDP growth of only 2.4 percent during 1997-2003. Weaker economic activity, the winding down of privatizations of public enterprises, and poor fiscal policy decisions (particularly on hydrocarbons) led to stagnant government revenue. Part II looks at the structure and trends of public expenditures, pointing that Bolivia's high indebtedness is an indication that the public sector is too large, considering the country's low level of revenue collection. The report explores the principal components of increased government spending, where by and large, wages, pensions, and interest payments amount to 70 percent of total revenues, and have increased by around 20 percent of GDP since 1998. Capital spending (public investment) has also increased recently, and current spending is required to maintain these capital investments, i.e., they will have a future impact on the budget. Recommendations suggest addressing the current fiscal imbalance by implementing expenditure caps on total fiscal expenditure; proposing reforms to increase efficiency of pension cost administration; adjusting local prices of fuel in accordance to changes in international prices; and, deepening the civil service reform. In the long run, subsidies to diesel fuel for electricity generation should be eliminated, and, regressive health insurance fund subsidies should be reviewed.